ANALYSIS OF ADARA BAKERY MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) - Anggi Setia Ningsih; Ulvia Rahmi; Mauliza Amanda; Azhar; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial sector in the Indonesian economy, contributing to job creation and improving community well-being. One of the growing MSMEs in the food and beverage sector is Adara Bakery. This study aims to analyze the business management and profits of Adara Bakery. The research method used is a descriptive method with a case study approach. The data used are simple assumptions regarding revenue and operating costs. The analysis shows that Adara Bakery has good profit potential if cost management and marketing strategies are implemented effectively. By improving product quality and cost efficiency, Adara Bakery can develop sustainably and contribute to the community's economy.